Impact of Second-Trimester Maternal Serum Screening on Prenatal Diagnosis of Down Syndrome and the use of Amniocentesis in the Taiwanese Population - Chih-Ping Chen; Chen-Ju Lin; Wayseen Wang (Elsevier, 2005)
Objective: To investigate the impact of second-trimester maternal serum screening on prenatal diagnosis of Down syndrome and the use of amniocentesis in the Taiwanese population. Materials and Methods: From 1990 to 2000, 166,419 amniocenteses were analyzed cytogenetically in the Taiwanese population. Among these, 58.85% were for advanced maternal age, 4.5% for abnormal ultrasound findings, 26.17% for abnormal maternal serum screening results, 1.82% for a previous child with congenital anomaly, 1.02% for a family history of chromosome aberrations, and 7.63% for other purposes. Chromosome aberrations were detected in 4,217 cases (2.53%), of which 1,277 (30.28%) were Down syndrome. Of the Down syndrome cases, 65.86% were detected by amniocentesis for advanced maternal age, 5.95% for abnormal ultrasound findings, 21.14% for abnormal maternal serum screening results, 1.25% for a previous child with congenital anomaly, 1.18% for a family history of chromosome aberrations, and 4.62% for other purposes. Results: There was a prominent increase in the number of women undergoing amniocentesis in the Taiwanese population between 1990 and 2000. There was an 8.9-fold increase in the number undergoing amniocentesis for advanced maternal age, a 6.3-fold increase in that for abnormal ultrasound findings, a 46.2-fold increase in that for abnormal maternal serum screening results, a 2.9-fold increase in that for a previous child with congenital anomaly, a 5.6-fold increase in that for a family history of chromosome aberrations, and a 4.4- fold increase in that for other purposes. There was also a 35.7-fold increase in the number of prenatally detected Down syndrome cases, from seven in 1990 to 250 in 2000. The highest rates of Down syndrome were found in cases with abnormal ultrasound findings (1/99 tests). Down syndrome was 0.72-fold as common in amniocenteses performed because of positive serum screening results (1/161 tests) compared with the rate seen in the advanced maternal age group (1/116 tests). The detection rates increased from 1/449 tests in 1990, through 1/198 tests, 1/203 tests, 1/158 tests, 1/215 tests, 1/229 tests, 1/169 tests, 1/143 tests, 1/90 tests, 1/92 tests, to 1/123 tests in 2000. Conclusion: Both the number of women undergoing amniocentesis and the number of detected cases of Down syndrome increased during these years. Amniocentesis in this population no longer led to a significant improvement in the detection rate of Down syndrome. In view of the effective use of amniocentesis as a diagnostic procedure for Down syndrome, efforts should be made to use more efficient prenatal screening programs and to reduce the number of unnecessary amniocenteses.